Carbon Dioxide (CO2) Absorption Potential Of Trees In Agrosilviculture Plantations In Wanseriwu Village, Tiworo Tengah District, West Muna Regency - Tuwu, Eka Rahmatiah; Indriyani, Lies; Midi, La Ode; Siwi, La Ode; Davik, Davik; Wati, Puja; Gandri, La (Universitas Jember, 2026)
Carbon is one of the fundamental elements forming organic matter, including living organisms, with nearly half of their biomass composed of carbon. Naturally, carbon is stored more abundantly in terrestrial and marine ecosystems than in the atmosphere, and its presence dates back to the formation of the Earth. This study aims to assess the carbon sequestration potential of agroforestry plants in Wanseriwu Village, Tiworo Tengah Subdistrict, West Muna Regency, in September 2025. The variables measured were tree diameter and total plant height. A non-destructive sampling method was applied, measuring diameter at breast height (DBH) and total plant height to estimate biomass using allometric equations, which were then converted into carbon absorption and storage data. Sampling intensity was set at 2%, with each plot measuring 20 × 20 m, from a total research area of 28 ha. Thus, the total sample area was 0.56 ha, consisting of 14 plots. The results revealed that the potential carbon sequestration of agrosilviculture plants in Wanseriwu Village reached 3,136.99 tonnes of CO₂ per year, with a carbon content of 854.76 tonnes per hectare. The high carbon value was influenced by the limited diversity of plant species, with only 10 types of vegetation recorded, as well as the lack of variation in tree age and size. These findings highlight the importance of agroforestry management in enhancing carbon sequestration capacity, while also emphasizing that vegetation diversity and stand structure play a crucial role in determining the carbon storage potential of an area.